2000
DOI: 10.1007/s11661-000-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

A model for nonclassical nucleation of solid-solid structural phase transformations

Abstract: A new model for homogeneous nucleation of structural phase transformations, which can span the range of nucleation from classical to nonclassical, is presented. This model is extended from the classical nucleation theory by introducing driving-force dependencies into the interfacial free energy, the misfit strain energy, and the nucleus chemical free-energy change in order to capture the nonclassical nucleation phenomena. The driving-force dependencies are determined by matching the asymptotic solutions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Quantity c=R introduces a``length scale'', and is neglected in this study, since it is mostly of relevance only in the case of nucleation, see e.g [8,9]. Finally, one can formulate a relation…”
Section: Jump Conditions Thermodynamic Force On the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Quantity c=R introduces a``length scale'', and is neglected in this study, since it is mostly of relevance only in the case of nucleation, see e.g [8,9]. Finally, one can formulate a relation…”
Section: Jump Conditions Thermodynamic Force On the Interfacementioning
confidence: 99%
“…The question remains, which process is responsible for the generation of a nucleus with the radius R i or, in reality, the midrib of a plate or lens. We leave this question to the studies [8,9], which investigated the nucleation problem applying a Helmholtz free-energy function, supplemented by a strain-gradient term to bridge the gap to atomistic dimensions. Since the study dealt with a spherically symmetric con®guration, the accommodation of the transformation shear is not included in their approach.…”
Section: Introductionmentioning
confidence: 99%
“…They denominated this type of nucleation as 'localized soft mode'. Later, the initial concept of heterogeneous dynamical nucleation was further consolidated with the efforts of Cao [40][41], Reid [36,[43][44][45], Chu [47], van Zyl [48][49] and Gröger [50] et al Based on the dynamical twinning [37], Reid et al [43] extensively analyzed the dynamical nucleation with a predefined local strain field (as an analog of heterogeneous nucleus) along with generalized boundary conditions. Their results demonstrated that the variation of morphology in MT, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al 18 examined the effect of spatially nonlocal interactions on the critical nucleus profile and nucleation rate employing the phase-field approach. Chu et al 19 developed a model to study the nonclassical nucleation behavior during structural transformations by introducing driving force dependencies into the interfacial energy, misfit strain energy, and nucleus chemical free energy change.…”
Section: Introductionmentioning
confidence: 99%